การสังเคราะห์ซีโอไลต์จากเถ้าลอยถ่านหินและจากเถ้าลอยชานอ้อย เพื่อการกำจัดตะกั่วในน้ำเสียอุตสาหกรรมจากโรงงานผลิตตะกั่วแท่ง : รายงานผลการวิจัย - ธเรศ ศรีสถิตย์ (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
The objective of this research was to study the possibility and applicability in zeolite syntheses using coal fly ash and bagasse fly ash which have been activated by Spent alkaline from black oxide coating industry compared with sodium hydroxide solution. This study designedly ascertained the optimum condition of zeolite syntheses comparatively from coal fry ash and bagasse fly ash. The optimum condition was determined by evaluating a cation exchange capacity (CEC) of the synthesized zeolite. The result revealed that the optimum condition exhibiting the highest CEC for synthesized zeolite using coal fly ash and bagasse fly ash were 418.36 cmol/kg and 286.29cmol/kg, characterized by reaction temperature of 90 degree Celsius, activation by Spent alkaline solution concentrated of 2.0 molars and reaction time of 5 days. Lead removal by using these optimally synthesized zeolites was evaluated with batch test. The batch experiment was utilized to study the influential factors on lead removal from synthetic wastewater which are namely pH favorableness, concentration of the heavy metal, contact time and adsorption isotherm. The outcomes were that the best adsorption efficiency of lead were at pH 5 and concentration of 10 mg/l of lead. From Langmuir adsorption isotherm of synthetic wastewater, it was found that the lead adsorption capacities of zeolites synthesized from coal fly ash and bagasse fly ash, which have been activated by Spent alkaline, were 78.31 and 65.23mg/g of zeolite respectively. Lead removal capacities of wastewater from Lead Ingots Factory using zeolites synthesized from coal fly ash and bagasse fly ash activation by Spent alkaline were 92.86% and 89.56% respectively. It can conclude that, Spent alkaline can used to activated zeolites instead of sodium hydroxide solution (NaOH).